Financial Ratio-Based Risk Assessment of Musharakah Financing in Indonesian Islamic Banking: The Moderating Role of Sharia Compliance - Muslih Muslih; Saparuddin Siregar; Kamilah K (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the effect of financial ratios on musharakah financing risk in Islamic banks in Indonesia, with sharia compliance positioned as a moderating variable. The study develops an explanatory model linking bank financial performance, represented by key financial ratios, to the level of risk associated with musharakah-based financing. Using secondary data obtained from the annual financial reports of Islamic commercial banks in Indonesia, this study applies a quantitative approach to evaluate the relationship between financial ratios, sharia compliance, and musharakah financing risk. The analysis is conducted by employing moderated regression analysis or panel data regression to capture both the direct effects of financial ratios and the interaction effect of sharia compliance. The findings are expected to show that financial ratios play an important role in explaining variations in musharakah financing risk, indicating that bank liquidity, profitability, capital adequacy, and financing quality are closely related to risk exposure in profit-sharing financing contracts. Furthermore, sharia compliance is expected to moderate the relationship between financial ratios and musharakah financing risk, suggesting that stronger adherence to Islamic principles may improve risk control and enhance the quality of financing governance. The novelty of this study lies in integrating financial ratio analysis with sharia compliance as a moderating mechanism in the context of musharakah financing risk. Practically, the findings may assist Islamic banks, regulators, and sharia supervisory boards in strengthening financial risk management while maintaining compliance with Islamic banking principles.